Gender quotas on boards of directors - Nina Smith (IZA World of Labor, 2014)
Arguments for increasing gender diversity on boards of directors range from ensuring equal opportunity to improving firm performance, but the empirical results are mixed and often negative. Current research does not justify gender quotas on grounds of economic efficiency. Furthermore, in most countries the number of women qualified to join boards of directors is limited, and it is not clear from the evidence that quotas lead to a larger pool of qualified female candidates in the medium and long term.
Keywords: G34; J16; L25; 330; gender quotas; boards of directors; firm performance